The Effect of Knowledge, Behavior, Religiousness on the Performance of Baitul Maal wa Tamwil - Mohamad Nawawi; Sri Fadilah; Nurleli Nurleli (Yayasan Riset dan Pengembangan Intelektual, 2024)
This research aims to investigate the influence of knowledge, behavior, and religiosity on the implementation of Sharia accounting and the performance of Islamic Cooperatives (BMT) in Purwakarta and Karawang Districts. The study involved 144 board members from 26 BMTs located in the two districts. The research method used was quantitative analysis with Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis. The results of the study showed significant and consistent findings with the research hypotheses. Firstly, knowledge has a significant impact on the performance of BMTs. This means that the higher the level of knowledge of BMT board members about Sharia accounting, the better the performance of the BMT. Secondly, behavior also has a significant influence on the performance of BMTs. This indicates that the more positive the behavior of board members in implementing Sharia accounting, the higher the performance of the BMT. Thirdly, religiosity also has a significant impact on the performance of BMTs. The study shows that the higher the level of religiosity of BMT board members, the better the performance of the BMT. The results of this research have impact on BMTs in improving their performance. BMT board members need to enhance their knowledge of Sharia accounting through appropriate training and education. Additionally, BMTs should promote positive behavior and prioritize religious values in the implementation of Sharia accounting. A better understanding of these factors is expected to enhance the performance of BMTs and serve as a guide for the development of BMTs in the future.